Impact of certain essential oils and insecticides against major insect pests and natural enemies in rice - Seni, Atanu (Journal of Cereal Research, 2019)
The present experiment was carried out during kharif, 2017 & 2018 to determine the efficacy of some selected botanicals (essential oils) and insecticides against major insect pests like stem borer; Scirpophaga incertulas (Walk.), plant hoppers; both brown plant hopper (BPH), Nilaparvata lugens (Stål), white backed plant hopper (WBPH), Sogatella furcifera (Horvath), gall midge; Orseolia oryzae (Wood-Mason) and natural enemies in rice. The treatments were; Camphor oil, Cedar wood oil, Eucalyptus oil and Lemon grass oil @ 1000 ml ha-1, Neemazal 1EC @ 1000 ml ha-1, Rynaxypyr 20 SC @ 150 ml ha-1 and Dinotefuran 20 SG @ 200 g ha-1. Among the different treatments, chemical insecticide Rynaxypyr 20 SC @ 150 ml ha-1 was most effective to manage the infestation of stem borer and Dinotefuran 20 SG @ 200 g ha-1 against plant hoppers in both the years. Among botanicals, Eucalyptus oil @ 1000 ml ha-1 was found effective to suppress the incidence of yellow stem borer and plant hoppers as well as highest yield was recorded from same treatment. Whereas, Cedar wood oil @ 1000 ml ha-1 was found effective to reduce the incidence of gall midge. All the botanicals were safe to natural enemies. For this reason, these botanicals may provide an effective and eco-friendly alternate to conventional synthetic insecticides and can be incorporated in the integrated pest management programme of rice pests. DOI: https://doi.org/10.25174/2249-4065/2019/95533